Real-world impact and effectiveness of MenACWY-TT - Villena, Rodolfo; Kriz, Paula; Tin Tin Htar, Myint; Burman, Cindy; Findlow, Jamie; Balmer, Paul; Jodar, Luis (Human vaccines & immunotherapeutics, 2023)
In response to escalating cases of serogroup W (MenW) invasive meningococcal disease (IMD), multiple countries introduced quadrivalent conjugate MenACWY vaccines into their national immunization programs (NIPs). Here, we summarize the real-world impact and vaccine effectiveness (VE) data of MenACWY-TT from Chile, England, the Netherlands, and Australia. Incidence rate reductions (IRRs) and VE from baseline to post-NIP period were extracted from publications or calculated. After the administration of a single dose of MenACWY-TT, substantial IRRs of MenCWY were observed across the countries in vaccine-eligible age groups (83%-85%) and via indirect protection in non-vaccine-eligible age groups (45%-53%). The impact of MenACWY-TT was primarily driven by MenW IRRs, as seen in vaccine-eligible age groups (65%-92%) and non-vaccine-eligible age groups (41%-57%). VE against MenW was reported in vaccine-eligible toddlers (92%) in the Netherlands and in vaccine-eligible adolescents/young adults (94%) in England. These real-world data support the implementation and continued use of MenACWY-TT in NIPs.
Keywords: Invasive meningococcal disease; Humans; Anglie; Netherlands; meningokokové infekce; Nizozemsko; mladý dospělý; kombinované vakcíny; lidé; Meningococcal Infections; vaccine effectiveness; MenACWY-TT; England; meningococcal vaccine; Adolescent; Vaccines, Combined; vaccine impact; Young Adult; Austrálie; Australia; mladiství